2019
DOI: 10.1002/lt.25435
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3‐Dimensional Printing in Pediatric Living Donor Liver Transplantation: A Single‐Center Experience

Abstract: Three‐dimensional (3D) printing has been used to support organ transplantations. However, whether it helps remains unclear. This study aimed to present and assess the application of 3D‐printed liver models in pediatric living donor liver transplantation (LDLT). The 3D images were printed to touchable liver models with transparent liver parenchyma, specifically colored hepatic vessels, and biliary structures. A total of 30 consecutive recipients were enrolled in the study: 10 were operated on with the support o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…In LDLT for infants or neonates with a limited abdominal space, it is often necessary to reduce the volume of the graft in a complex manner to maintain the necessary vascular structures. Surgeons can simulate donor surgery through 3D images and 3D printed physical models; moreover, the 3D printed model provides a realistic sense of the size, vascular anatomy, and thickness of the reduced graft [52,78,82].…”
Section: Living Donor Liver Transplantation Guided By 3d Visualizationmentioning
confidence: 99%
“…In LDLT for infants or neonates with a limited abdominal space, it is often necessary to reduce the volume of the graft in a complex manner to maintain the necessary vascular structures. Surgeons can simulate donor surgery through 3D images and 3D printed physical models; moreover, the 3D printed model provides a realistic sense of the size, vascular anatomy, and thickness of the reduced graft [52,78,82].…”
Section: Living Donor Liver Transplantation Guided By 3d Visualizationmentioning
confidence: 99%
“…Zhao et al [59] Evaluation study Evaluation of a computer-assisted surgery system in preoperative surgical planning and intraoperative navigation…”
mentioning
confidence: 99%
“…Janek et al [58] Blood loss, blood transfusion, recurrence, bilirubin levels, the volume of post-resection liver residue Zhao et al [59] Operation time, blood loss, blood transfusion Wang et al [60] Operation time, blood loss, mortality, intra-and postoperative complications, inpatient stay, cost Esaki et al [61] Liver and spleen volume measurement Ishii et al [63] Operation time, blood loss, intraoperative complications…”
mentioning
confidence: 99%
“…The acceleration in LDLT experience in Asian countries was born out of necessity, but it has also been catalyzed by a concentration of volume and expertise, technical developments, and innovative approaches . In this issue of Liver Transplantation , Wang et al present their experience with 3‐dimensional (3D) printing of transparent liver models, and they compare outcomes with standard preoperative planning in a series of 30 children undergoing pediatric LDLT.…”
mentioning
confidence: 99%
“…Wang et al found 3D printing to be useful in surgical planning especially in the management of hepatic venous anatomic variations, calculations of graft and recipient weights, and determination of spatial orientation and capacity in the abdominal cavity. Of the 10 grafts that used 3D printing, 3 were considered more complex (left lobe, reduced right lobe without the middle hepatic vein, and auxiliary partial orthotopic liver transplantation with a left lobe graft) than the 7 left lateral segment grafts.…”
mentioning
confidence: 99%